AUTOLOGOUS LENS CAPSULAR FLAP TRANSPLANTATION COMBINED WITH AUTOLOGOUS BLOOD APPLICATION IN THE MANAGEMENT OF REFRACTORY MACULAR HOLE. Issue 11 (November 2018) - Peng, Jie; Chen, Chunli; Jin, Haiying; Zhang, Hongtao; Zhao, Peiquan
Abstract : Purpose: To report results of lens capsular flap transplantation (LCFT) and autologous whole blood application in refractory macular hole (MH) treatment. Methods: Seven phakic and three aphakic eyes with persistent MH after standard surgery with internal limiting membrane peeling were studied. Lens capsule flap was acquired from the same eye in eight cases (seven phakic and one aphakic). The fellow eye was used in two aphakic eyes without sufficient lens capsule. The fellow eye underwent simultaneous phacoemulsification. All eyes underwent complete vitrectomy, LCFT into the MH, whole blood application, and 15% perfluoropropane (C3 F8 ) tamponade. The patients were instructed to maintain a face-down or prone position for two weeks postoperatively. Structural and functional changes were evaluated. Results: The mean preoperative MH diameter was 1, 472.78 ± 736.88 μ m. The MH was completely closed in nine eyes: eight eyes receiving same-eye LCFT and one receiving fellow-eye LCFT. In the other fellow-eye LCFT recipient, the MH was partially closed. Visual acuity improved from 1.84 ± 0.49 logarithm of the minimum angle of resolution (median Snellen acuity: 20/1, 750, range: 20/4, 000–20/125) preoperatively to 1.34 ± 0.59 logarithm of the minimum angle of resolution (median Snellen acuity: 20/450, range: 20/4, 000–20/63) postoperatively ( P = 0.009). Conclusion: Lens capsular flap transplantation and autologous whole blood application may improve anatomical and visual outcomes in refractory MH cases. The lens equator and fellow eye may be promising sources of LCF. Abstract : Supplemental Digital Content is Available in the Text.The authors report the outcomes of autologous lens capsular flap transplantation combined with autologous whole blood application for refractory macular hole. For the first time ever, lens capsular flap was harvested from the lens equator and from the fellow eye, which may be promising sources of lens capsular flap for aphakic or pseudophakic eyes.